Foundations of Security Analysis and Design VI FOSAD Tutorial Lectures - Aldini, Alessandro; Gorrieri, Roberto; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
FOSAD has been one of the foremost educational events established with the goal of disseminating knowledge in the critical area of security in computer systems and networks. Offering a timely spectrum of current research in foundations of security, FOSAD also proposes panels dedicated to topical open problems, and giving presentations about ongoing work in the field, in order to stimulate discussions and novel scientific collaborations. This book presents thoroughly revised versions of nine tutorial lectures given by leading researchers during three International Schools on Foundations of Security Analysis and Design, FOSAD, held in Bertinoro, Italy, in September 2010 and August/September 2011. The topics covered in this book include privacy and data protection; security APIs; cryptographic verification by typing; model-driven security; noninterfer-quantitative information flow analysis; and risk analysis.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Logic design; Information Systems; Computer Science; Systems and Data Security; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters